Circular RNA hsa_circ_0000700 promotes cell proliferation and migration in Esophageal Squamous Cell Carcinoma by sponging miR-1229 - Fang, Jun (J Cancer, 2021)
Accumulating evidence has demonstrated that circular RNAs (circRNAs) are involved in the pathogenesis of cancer, including that of esophageal squamous cell carcinoma (ESCC). The current study aimed to investigate the role of hsa_circ_0000700 in ESCC. hsa_circ_0000700, miR-1229, and related functional gene expression was measured by RT-qPCR. To characterize the functions of hsa_circ_0000700 and miR-1229, ESCC cells were infected with hsa_circ_0000700-specific siRNA, miR-1229 mimics, and an inhibitor alone or in combination. Cell Counting Kit-8 (CCK8), colony formation, EdU, flow cytometry, and Transwell assays were employed to evaluate cell proliferation, apoptosis, and migration. Luciferase reporter and RNA immunoprecipitation assays were used to confirm the targeting relationship between hsa_circ_0000700 and miR-1229. Finally, a competing endogenous RNAs (ceRNA) network was built for hsa_circ_0000700, and miR-1229 targets were analyzed by bioinformatics. circ_0000700 expression was significantly upregulated in ESCC cell lines. Actinomycin D and RNase R treatment confirmed that circ_0000700 was more stable than its linear CDH9 mRNA form. Moreover, a cytoplasmic and nuclear fractionation assay suggested that circ_0000700 was mainly distributed in the cytoplasm of ECA-109 and TE-1 cells. In vitro, the proliferative and migratory capacities of ECA-109 and TE-1 cells were inhibited by knocking down circ_0000700 expression. Additionally, miR-1229 silencing reversed the circ_0000700-specific siRNA-induced attenuation of malignant phenotypes. Mechanistically, circ_0000700 was identified as a sponge of miR-1229 and could activate PRRG4, REEP5, and PSMB5 indirectly to promote ESCC progression. In summary, our results suggest that hsa_circ_0000700 functions as an oncogenic factor by sponging miR-1229 in ESCC.